Edicta munerum: Advertising and Promotion of Gladiatorial Games in Ancient Pompeii - Miączewska, Anna (Brill Studies in Greek and Roman Epigraphy, 2025)
Edicta munerum: Advertising and Promotion of Gladiatorial Games in Ancient Pompeii delves into the intriguing realm of behind-the-scenes preparations for the gladiatorial games in ancient Pompeii, shedding light on how advertising played a pivotal role in informing and enticing the public to witness gladiators engage in life-and-death combat. By examining epigraphic evidence, the book highlights the spatial and aesthetic significance of inscriptions as ancient means of conveying information about mass events held in the local amphitheatres. This study demonstrates that the world of advertising was well-established and thriving over two millennia ago.